EFFECTIVENESS OF E-LEARNING IN TEACHING ISLAMIC CHEMISTRY: BUILDING AN ISLAMIC SOCIETY WITH COMPREHENSIVE UNDERSTANDING OF CHEMISTRY AND ISLAMIC VALUES - Sidiq, Heri Purwanto Sidiq; Sauri, Sofyan; Bahruddin, Ending; Handrianto, Budi (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2023)
This research investigates the effectiveness of e-learning methods in teaching Islamic chemistry and their contribution to fostering an Islamic society with a comprehensive understanding of chemistry and Islamic values. The study focuses on the integration of Islamic values into chemistry education using online learning platforms. Adopting a qualitative approach with a case study design, the research involves students participating in an e-learning program for Islamic chemistry. Data is collected through observations, interviews, and document analysis to explore students' interactions with the e-learning platform and their responses to the integration of Islamic values. Thematic analysis is employed for data analysis. The findings highlight the significant impact of e-learning methods in teaching Islamic chemistry, enhancing students' understanding of both the subject matter and Islamic values. The integration of Islamic values in chemistry education promotes a deeper comprehension of the connections between chemistry and Islamic teachings. However, challenges such as technical issues and effective online communication need to be addressed.